2000
DOI: 10.1117/12.411726
|View full text |Cite
|
Sign up to set email alerts
|

<title>Distributed temperature sensing (DTS) to characterize the performance of producing oil wells</title>

Abstract: This paper describes how distributed temperature sensing (DTS) based on Raman Scattering is being used as an in-situ logging technique in oil & gas wells. Traditional methods of gathering production data to characterize oil & gas well performance have relied on the introduction of electric logging tools into the well. This can be an expensive process in highly deviated or horizontal wells and usually results in the well being shut-in with the loss or deferment of hydrocarbon production. More recently permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Furthermore, it has been observed that flushing the cable could significantly contribute to a reduction of harmful chemical species (e.g. hydrogen released from the cable itself due to cracking of forming oil at elevated temperatures Williams et al, 2000; along the cable and therefore increase the lifetime of the installation at high temperatures.…”
Section: Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been observed that flushing the cable could significantly contribute to a reduction of harmful chemical species (e.g. hydrogen released from the cable itself due to cracking of forming oil at elevated temperatures Williams et al, 2000; along the cable and therefore increase the lifetime of the installation at high temperatures.…”
Section: Conceptmentioning
confidence: 99%
“…The ingression of hydrogen and the subsequent formation of hydroxyl causes strong absorption peaks at relevant wavelengths (Stone and Walrafen, 1982;Humbach et al, 1996;Williams et al, 2000). The increasing absorption at individual wavelengths leads to an increase in the differential attenuation between the Stokes and Anti-Stokes band.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both can be many kilometers long and have found use in measuring temperature within oil wells (Williams et al 2000) and along power cables serving offshore wind farms (Fromme et al 2011), as well as strain within infrastructure such as tunnels and pipelines (Rajeev et al 2013). Brillouin systems can achieve spatial resolution down to ~1 cm, while Raman is limited to ~1 m; time response is generally on the order of minutes (Bao and Chen 2012) though some commercial systems can now achieve data rates of approximately 1 Hz.…”
Section: Sensing With Scattered Lightmentioning
confidence: 99%
“…By far the more common type is the Raman backscattering reflectometer, which measures spontaneous Raman scattering (SRS). SRS is useful because the anti-Stokes Raman band is temperature-sensitive, and can be referenced against the comparatively insensitive Stokes Raman band (Williams et al 2000). A third type is a Brillouin backscattering reflectometer (Rogers 1999).…”
Section: Fundamentals Of Operationmentioning
confidence: 99%